MAKNA TRADISI DUI’ MENRE’ / UANG PANAI’ DI KOTA MANADO (Studi Kasus Perkawinan Eksogami Perantau Pria Bugis-Makassar di Manado) - Damis, Mahyudin (Universitas Sam Ratulangi, 2020)
This paper examines the meaning of dui 'menre' or panai money 'in exogamous marriages among Bugis-Makassar male migrants in Manado. Traditionally, an endogamous marriage is a marriage that is considered ideal for the people of these ethnic groups in their area of origin. The results of this study indicate that the Bugis-Makassar male migrants in Manado have a set of knowledge or categorization, namely; where is dui 'menre' or panai money 'and which is also called dowry or sompa which must be fulfilled according to Islamic law. By having this categorization ability, the dowry or marriage ceremony is what they prioritize over dui 'menre' or panai money 'because dowry is a religious commandment (Islam) that they adhere to. The viewpoint of male BugisMakassar immigrants when marrying other ethnic groups in Manado is that they are no longer obliged to give dui’ menre’ or uang panai’ to women due to several reasons.Keywords: Exogamous Marriage, Bugis-Makassar Migrants, dui menre' / uang panai